Flame-retardant polyurethane repair adhesive and repair method

By developing a flame-retardant polyurethane repair glue containing prepolymer master glue, amine-containing mixed solution and reactive mixed solution, the existing repair glue is solved, and the problem of easy shelf life and lack of flame retardant performance is achieved, and a fast, strong and flame retardant repair effect is achieved.

CN119614136APending Publication Date: 2025-03-14WUXI BOTON CONVEYOR SOLUTION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411829545.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing polyurethane repair glue is prone to falling off during use, the repair shelf life is short, and it lacks flame retardant performance, so it cannot be used in areas such as coal and other required flame retardant.

Method used

A flame-retardant polyurethane repair glue is developed, including prepolymer master glue A, mixed solution B containing amines and mixed solution C containing reactive activity. By optimizing component ratio and formula, the bonding strength and flame retardant properties of the repair glue are improved.

Benefits of technology

It achieves the repair effect of fast repair speed, high bonding strength and good flame retardant performance, extends the service life of the repair glue, and is suitable for flame retardant conveyor belts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a flame-retardant polyurethane repair adhesive and a repair method. The flame-retardant polyurethane repair adhesive comprises a prepolymer masterbatch component A, a mixed solution component B containing amines and a mixed solution component C containing reactivity which are independently packaged, the repairing method comprises the following steps: cleaning, polishing, and mixing the component C of the mixed solution containing reactivity, the component B of the mixed solution containing amines and the component A of the prepolymer masterbatch according to the mass ratio of (40-50): 100 to form polyurethane and repairing. The curing time is short, the operation waiting time for repairing the conveying belt can be shortened, and the standby consumption is reduced. The cured repair adhesive has excellent strength and wear resistance, and can bear material impact wear as a structural repair material, thereby prolonging the service life of the damaged conveyor belt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of repair adhesives, and specifically discloses a flame retardant polyurethane repair adhesive and a repair method. Background Art

[0002] During the use of conveyor belts, after long-term high-load operation, problems such as wear and tear often occur. Timely repairs are required to avoid transportation interruptions and / or transportation accidents caused by the expansion of conveyor belt damage. Timely repairs are also conducive to extending the life of the conveyor belt. Polyurethane repair adhesive products are widely used in the rubber conveyor belt industry for simple and quick repairs of conveyor belts. Due to its excellent performance, polyurethane adhesives are often selected as repair adhesives for on-site rapid repairs of rubber wear. However, the performance of existing products is relatively low. During use, the repair block is prone to fall off, resulting in a short shelf life of the repair. In addition, they generally do not have flame retardant properties and cannot be used in flame retardant fields such as coal, which poses certain risks. Summary of the invention

[0003] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a flame retardant polyurethane repair adhesive and a repair method which have a fast repair speed and have both high bonding strength and flame retardant properties after repair.

[0004] According to the technical solution provided by the present invention, the flame retardant polyurethane repair adhesive comprises a separately packaged prepolymer masterbatch component A, a mixed solution component B containing amines, and a mixed solution component C containing reactive agents, wherein the mass ratio of the prepolymer masterbatch component A to the mixed solution component B containing amines is 100:(40-50);

[0005] The prepolymer masterbatch component A comprises the following components premixed together in a mass ratio of (80-100):(1-10):(1-5):prepolymer, organic solvent and dye;

[0006] The mixed solution B containing amines comprises the following components pre-mixed together in a mass ratio of (15-35):(1-5):(1-10): a composite cross-linking agent, a composite catalyst and a composite flame retardant antistatic agent;

[0007] The reactive mixed solution component C includes the following components in a mass ratio of (1-2):(1-2):(0.5-3):(0.2-0.8):(1-3):(40-50):(40-50):trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate, fumed silica, ethyl acetate and trichloroethylene.

[0008] Preferably, the prepolymer is an isocyanate-terminated polymer material having a molecular weight of 500-3000 and formed by the reaction of a diol and a diisocyanate.

[0009] Preferably, the organic solvent comprises one or more of ethyl acetate, isobutyl acetate, butanone, and methyl isobutyl ketone.

[0010] Preferably, the coloring agent includes one of carbon black N330 and carbon black N550.

[0011] Preferably, the composite cross-linking agent comprises the following components pre-mixed together in a mass ratio of (5-10):(5-10):(5-15):(2-5): a solid amine cross-linking agent, a liquid amine cross-linking agent, ethyl acetate and trichloroethylene;

[0012] The solid amine cross-linking agent includes one or more of 3,3'-dichloro-4,4'-diaminodiphenylmethane, 4,4'-bis-sec-butylaminodiphenylmethane, N,N'-bis-sec-pentylcyclohexanediamine and pentaerythritol.

[0013] The liquid amine crosslinking agent includes dimethylthiotoluene diamine, 2,4-diamino-3,5-dimethylthiotoluene 、 One or more of N,N-bis(2-hydroxypropyl)aniline and N,N,N`,N`-tetra(2-hydroxypropyl)ethylenediamine.

[0014] Preferably, the composite catalyst comprises the following components pre-mixed together in a mass ratio of (0.5-3): (0.5-3): an organic metal catalyst and a defoaming agent;

[0015] The organometallic catalyst includes one or more of zinc isooctanoate, dibutyltin dilaurate, lithium isooctanoate, and lead isooctanoate;

[0016] The defoaming agent includes one or more of a silicone resin defoaming agent, a methanol defoaming agent, an ethanol defoaming agent, an isopropanol defoaming agent, a polypropylene glycol defoaming agent, a n-butanol defoaming agent, and a tributyl phosphate defoaming agent.

[0017] Preferably, the composite flame retardant and antistatic agent comprises the following components pre-mixed together in a mass ratio of (1-5):(1-3):(1-3):phosphorus-based flame retardant, antistatic agent and carbon black VXC72.

[0018] The phosphorus-based flame retardant includes one or more of tris(2-chloroethyl)phosphate, tris(2-chloropropyl)phosphate, dimethyl methylphosphonate, and diethyl ethylphosphate;

[0019] The antistatic agent includes one or more of antistatic agent KJ-100, antistatic agent KJ-150, and antistatic agent KJ-208.

[0020] A method for repairing rubber using the flame retardant polyurethane repair adhesive comprises the following steps:

[0021] S1. First, use a solvent to clean the rubber surface to be repaired, and then polish the rubber surface to be repaired to remove the residual rubber and oil on the surface;

[0022] S2. Prepare the following components in a mass ratio of (1-2):(1-2):(0.5-3):(0.2-0.8):(1-3):(40-50):(40-50): trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate, fumed silica, ethyl acetate and trichloroethylene, mix ethyl acetate and trichloroethylene to form a premixed solvent, dissolve trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate and fumed silica in the premixed solvent and mix well to obtain a mixed solution component C containing reactive activity;

[0023] S3, evenly apply the reactive mixed solution component C to the polished part of the rubber surface to be repaired, and apply 1 to 3 ml of the reactive mixed solution component C per 100 square centimeters of area each time. Apply it again after the first application, and dry it naturally after each application to increase the adhesion between the polyurethane and the surface to be repaired;

[0024] S4, mixing the mixed solution component B containing amines and the prepolymer masterbatch component A in a mass ratio of (40-50):100 to form a polyurethane;

[0025] S5. Apply a thin layer of the newly mixed polyurethane to the polished area on the rubber surface to be repaired, let it stand for 0.5 to 5 minutes, pour the remaining polyurethane on the polished area on the rubber surface to be repaired, and the repair is completed after the polyurethane solidifies.

[0026] The present invention has the following advantages:

[0027] 1. It has a shorter curing time, which can shorten the waiting time for repairing the conveyor belt and reduce standby consumption.

[0028] 2. It can react quickly at room temperature, and the surface drying time is within 30 minutes, which improves the working efficiency of the conveyor belt.

[0029] 3. The cured repair adhesive has excellent strength and wear resistance. As a structural repair material, it can withstand material impact wear, thereby extending the service life of the damaged conveyor belt.

[0030] 4. The mixed solution B contains a compounded antistatic agent and a flame retardant, which increases the flame retardant and antistatic properties of the material, making it applicable to flame retardant conveyor belts.

[0031] 5. Adding reactive mixed solution C to the formula enhances the bonding strength between polyurethane and the conveyor belt, reduces the risk of the repair block falling off, and extends the service life of the repair glue. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0033] The prepolymer used in the following examples is provided by Jiangsu Qianmeite Polyurethane New Materials Co., Ltd., and the product model is K1221.

[0034] Example 1

[0035] A flame retardant polyurethane repair adhesive, comprising a prepolymer masterbatch component A, a mixed solution component B containing amines and a mixed solution component C containing reactive substances, wherein the mass ratio of the prepolymer masterbatch component A to the mixed solution component B containing amines is 100:41;

[0036] Prepolymer K1221, ethyl acetate, butanone, and carbon black N330 were mixed uniformly in a mass ratio of 88:6:4:2 to form prepolymer masterbatch component A;

[0037] Prepare the following materials in a mass ratio of 5:5:5:10:2:2:2:8:1:1: solid crosslinking agent 3,3'-dichloro-4,4'-diaminodiphenylmethane, solid crosslinking agent N,N'-di-sec-pentylcyclohexanediamine, liquid crosslinking agent N,N-bis(2-hydroxypropyl)aniline, ethyl acetate, trichloroethylene, zinc isooctanoate catalyst, silicone resin defoamer, tris(2-chloroethyl)phosphate, carbon black VXC72 and antistatic agent KJ-100;

[0038] Among them, the solid crosslinking agent 3,3'-dichloro-4,4'-diaminodiphenylmethane, the solid crosslinking agent N,N'-di-sec-pentylcyclohexanediamine, the liquid crosslinking agent N,N-bis(2-hydroxypropyl)aniline, ethyl acetate and trichloroethylene form a composite crosslinking agent; the zinc isooctanoate catalyst and the silicone resin defoaming agent form a composite catalyst; tri(2-chloroethyl) phosphate, carbon black VXC72 and antistatic agent KJ-100 form a composite flame retardant antistatic agent; the composite crosslinking agent, the composite catalyst and the composite flame retardant antistatic agent form a mixed solution B component containing amines;

[0039] Prepare the following substances that can form the reactive mixed solution component C in a mass ratio of 50:50:1:1.5:3:0.8:1: ethyl acetate, trichloroethylene, trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate and fumed silica;

[0040] A method for repairing rubber using the flame retardant polyurethane repair adhesive comprises the following steps:

[0041] S1. First, use a solvent to clean the rubber surface to be repaired, and then polish the rubber surface to be repaired to remove the residual rubber and oil on the surface;

[0042] S2, ethyl acetate and trichloroethylene are mixed evenly to form a premixed solvent, trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate and fumed silica are dissolved in the premixed solvent and mixed evenly to obtain a mixed solution component C containing reactive activity;

[0043] S3, evenly apply the reactive mixed solution component C to the polished part of the rubber surface to be repaired, and apply 2 ml of the reactive mixed solution component C per 100 square centimeters of area each time. Apply it again after the first application, and dry it naturally after each application to increase the adhesion between the polyurethane and the surface to be repaired;

[0044] S4, the prepolymer masterbatch component A and the mixed solution component B containing amines are mixed evenly to form a polyurethane, the operable time of the polyurethane is 6 minutes, the basic curing time of the polyurethane is 50 minutes, and part of the polyurethane is placed at room temperature for 24 hours to obtain a polyurethane elastomer, and flame retardant effect, tensile strength and abrasion tests are performed. The test results are shown in Table 1;

[0045] S5. Apply a thin layer of the mixed polyurethane to the polished area of ​​the rubber surface to be repaired, let it stand for 3 minutes, pour the remaining polyurethane on the rubber surface to be repaired, and complete the repair after the polyurethane solidifies. Perform a bonding strength test after 24 hours. The test results are shown in Table 1.

[0046] Example 2

[0047] A flame retardant polyurethane repair adhesive, comprising a prepolymer masterbatch component A, a mixed solution component B containing amines and a mixed solution component C containing reactive substances, wherein the mass ratio of the prepolymer masterbatch component A to the mixed solution component B containing amines is 100:46;

[0048] Prepolymer K1221, ethyl acetate, methyl isobutyl ketone and carbon black N330 were uniformly mixed in a mass ratio of 90:4:4:2 to form prepolymer masterbatch component A;

[0049] Prepare the following materials in a mass ratio of 8:5:4:5:5:3:1:10:2:1: solid crosslinking agent 4,4'-bis-sec-butylaminodiphenylmethane, liquid crosslinking agent 2,4-diamino-3,5-dimethylthiotoluene, liquid crosslinking agent N,N-bis(2-hydroxypropyl)aniline, ethyl acetate, trichloroethylene, dibutyltin dilaurate catalyst, methanol defoamer, ethanol defoamer, tris(2-chloropropyl)phosphate, carbon black VXC72 and antistatic agent KJ-150;

[0050] Among them, a solid crosslinking agent 4,4'-bis-sec-butylaminodiphenylmethane, a liquid crosslinking agent 2,4-diamino-3,5-dimethylthiotoluene, a liquid crosslinking agent N,N-bis(2-hydroxypropyl)aniline, ethyl acetate and trichloroethylene form a composite crosslinking agent, a dibutyltin dimethyl silicate catalyst, a methanol defoamer and an ethanol defoamer form a composite catalyst, tri(2-chloropropyl) phosphate, carbon black VXC72 and an antistatic agent KJ-150 form a composite flame retardant and antistatic agent, and the composite crosslinking agent, the composite catalyst and the composite flame retardant and antistatic agent form a mixed solution component B containing amines;

[0051] Prepare the following substances that can form the reactive mixed solution component C in a mass ratio of 45:50:1:1:1:0.4:1.5: ethyl acetate, trichloroethylene, trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate and fumed silica;

[0052] A method for repairing rubber using the flame retardant polyurethane repair adhesive comprises the following steps:

[0053] S1. First, use a solvent to clean the rubber surface to be repaired, and then polish the rubber surface to be repaired to remove the residual rubber and oil on the surface;

[0054] S2, ethyl acetate and trichloroethylene are mixed evenly to form a premixed solvent, trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate and fumed silica are dissolved in the premixed solvent and mixed evenly to obtain a mixed solution component C containing reactive activity;

[0055] S3, evenly apply the reactive mixed solution component C to the polished part of the rubber surface to be repaired, and apply 1.5 ml of the reactive mixed solution component C per 100 square centimeters of area each time. Apply it again after the first application, and dry it naturally after each application to increase the adhesion between the polyurethane and the surface to be repaired;

[0056] S4, the prepolymer masterbatch component A and the mixed solution component B containing amines are mixed evenly to form a polyurethane, the operable time of the polyurethane is 3 minutes, the basic curing time of the polyurethane is 30 minutes, and part of the polyurethane is placed at room temperature for 24 hours to obtain a polyurethane elastomer, and flame retardant effect, tensile strength and abrasion tests are performed. The test results are shown in Table 1;

[0057] S5. Apply a thin layer of the mixed polyurethane to the polished area of ​​the rubber surface to be repaired, let it stand for 5 minutes, pour the remaining polyurethane to the rubber surface to be repaired, and complete the repair after the polyurethane solidifies. Perform a bonding strength test after 24 hours. The test results are shown in Table 1.

[0058] Example 3

[0059] A flame retardant polyurethane repair adhesive, comprising a prepolymer masterbatch component A, a mixed solution component B containing amines and a mixed solution component C containing reactive substances, wherein the mass ratio of the prepolymer masterbatch component A to the mixed solution component B containing amines is 100:48;

[0060] Prepolymer K1221, isobutyl acetate, butanone, and carbon black N550 were uniformly mixed in a mass ratio of 85:5:5:5 to form prepolymer masterbatch component A;

[0061] Prepare the following materials in a mass ratio of 8:6:12:3:3:1:1:12:1:1:1:1: solid crosslinking agent N,N`-di-sec-pentylcyclohexanediamine, liquid crosslinking agent N,N,N`,N`-tetrakis(2-hydroxypropyl)ethylenediamine, ethyl acetate, trichloroethylene, lithium isooctanoate catalyst, isopropyl alcohol defoamer, polypropylene glycol defoamer, dimethyl methylphosphonate, carbon black VXC72 and antistatic agent KJ-208;

[0062] Among them, the solid crosslinking agent N,N'-di-sec-pentylcyclohexanediamine, the liquid crosslinking agent N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine, ethyl acetate and trichloroethylene form a composite crosslinking agent, the lithium isooctanoate catalyst, isopropyl alcohol defoaming agent and polypropylene glycol defoaming agent form a composite catalyst, and dimethyl methylphosphonate, carbon black VXC72 and antistatic agent KJ-208 form a composite flame retardant antistatic agent;

[0063] Prepare the following substances that can form the reactive mixed solution component C in a mass ratio of 50:45:1.5:1.5:3:0.6:2: ethyl acetate, trichloroethylene, trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate and fumed silica;

[0064] A method for repairing rubber using the flame retardant polyurethane repair adhesive comprises the following steps:

[0065] S1. First, use a solvent to clean the rubber surface to be repaired, and then polish the rubber surface to be repaired to remove the residual rubber and oil on the surface;

[0066] S2, ethyl acetate and trichloroethylene are mixed evenly to form a premixed solvent, trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate and fumed silica are dissolved in the premixed solvent and mixed evenly to obtain a mixed solution component C containing reactive activity;

[0067] S3, evenly apply the reactive mixed solution component C to the polished part of the rubber surface to be repaired, 3 ml of the reactive mixed solution component C is applied per 100 square centimeters of area each time, apply it again after the first application, and dry it naturally after each application to increase the adhesion between the polyurethane and the surface to be repaired;

[0068] S4, the prepolymer masterbatch component A and the mixed solution component B containing amines are mixed evenly to form a polyurethane, the operable time of the polyurethane is 4 minutes, the basic curing time of the polyurethane is 35 minutes, and part of the polyurethane is placed at room temperature for 24 hours to obtain a polyurethane elastomer, and flame retardant effect, tensile strength and abrasion tests are performed. The test results are shown in Table 1;

[0069] S5. Apply a thin layer of the mixed polyurethane to the polished area of ​​the rubber surface to be repaired, let it stand for 4 minutes, pour the remaining polyurethane on the rubber surface to be repaired, and complete the repair after the polyurethane solidifies. Perform a bonding strength test after 24 hours. The test results are shown in Table 1.

[0070] Example 4

[0071] A flame retardant polyurethane repair adhesive, comprising a separately packaged prepolymer masterbatch component A, a mixed solution component B containing amines, and a mixed solution component C containing reactive agents, wherein the mass ratio of the prepolymer masterbatch component A to the mixed solution component B containing amines is 100:45;

[0072] Prepolymer K1221, isobutyl acetate, methyl isobutyl ketone and carbon black N550 were mixed uniformly in a mass ratio of 86:8:2:4 to form prepolymer masterbatch component A;

[0073] Prepare the following materials in a mass ratio of 6:4:6:8:2:2:1:2:12:1:1:1: solid crosslinking agent 4,4'-bis-sec-butylaminodiphenylmethane, liquid crosslinking agent N,N'-bis-sec-pentylcyclohexanediamine, liquid crosslinking agent 2,4-diamino-3,5-dimethylthiotoluene, ethyl acetate, trichloroethylene, lead isooctanoate catalyst, n-butanol defoamer, tributyl phosphate defoamer, ethyl diethyl phosphate, carbon black VXC72 and antistatic agent KJ-208;

[0074] Among them, the solid crosslinking agent 4,4'-bis-sec-butylaminodiphenylmethane, the liquid crosslinking agent N,N'-bis-sec-pentylcyclohexanediamine, the liquid crosslinking agent 2,4-diamino-3,5-dimethylthiotoluene, ethyl acetate and trichloroethylene form a composite crosslinking agent, the lead isooctanoate catalyst, the n-butanol defoaming agent and the tributyl phosphate defoaming agent form a composite catalyst, and the ethyl diethyl phosphate, carbon black VXC72 and the antistatic agent KJ-208 form a composite flame retardant antistatic agent;

[0075] Prepare the following substances that can form the reactive mixed solution component C in a mass ratio of 40:40:1:1:0.5:0.2:1: ethyl acetate, trichloroethylene, trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate and fumed silica;

[0076] A method for repairing rubber using the flame retardant polyurethane repair adhesive comprises the following steps:

[0077] S1. First, use a solvent to clean the rubber surface to be repaired, and then polish the rubber surface to be repaired to remove the residual rubber and oil on the surface;

[0078] S2, ethyl acetate and trichloroethylene are mixed evenly to form a premixed solvent, trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate and fumed silica are dissolved in the premixed solvent and mixed evenly to obtain a mixed solution component C containing reactive activity;

[0079] S3, evenly apply the reactive mixed solution component C to the polished part of the rubber surface to be repaired, and apply 2.5 ml of the reactive mixed solution component C per 100 square centimeters of area each time. Apply it again after the first application, and dry it naturally after each application to increase the adhesion between the polyurethane and the surface to be repaired;

[0080] S4, the prepolymer masterbatch component A and the mixed solution component B containing amines are mixed evenly to form a polyurethane, the operable time of the polyurethane is 4 minutes, the basic curing time of the polyurethane is 35 minutes, and part of the polyurethane is placed at room temperature for 24 hours to obtain a polyurethane elastomer, and flame retardant effect, tensile strength and abrasion tests are performed. The test results are shown in Table 1;

[0081] S5. Apply a thin layer of the mixed polyurethane to the polished area of ​​the rubber surface to be repaired, let it stand for 1 minute, pour the remaining polyurethane to the rubber surface to be repaired, and complete the repair after the polyurethane solidifies. Perform a bonding strength test after 24 hours. The test results are shown in Table 1.

[0082] Table 1

[0083]

[0084]

[0085] It can be seen from Examples 1-4 that the flame-retardant polyurethane repair adhesive of the present invention can complete the repair in only 1 to 1.5 hours. Compared with hot vulcanization repair, the equipment preparation time is greatly shortened, and the operation waiting time for repairing the conveyor belt can be shortened. The prepolymer masterbatch component A in the present invention reacts with the mixed solution component B containing amines to generate polyurethane. The cured repair adhesive has excellent strength and wear resistance. As a structural repair material, it can withstand material impact wear, thereby extending the service life of the damaged conveyor belt. The mixed solution component B containing amines contains composite antistatic and flame retardants, which increases the flame retardant and antistatic properties of the material, so that it can be used in flame-retardant conveyor belts. The flame-retardant polyurethane repair adhesive of the present invention adds a mixed solution component C containing reactive activity in the formula structure, which enhances the bonding strength between the polyurethane and the conveyor belt, reduces the risk of the repair block falling off, and extends the service life of the repair adhesive.

[0086] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A flame retardant polyurethane repair adhesive, characterized in that: The method comprises a prepolymer masterbatch component A, a mixed solution component B containing amines and a mixed solution component C containing reactive substances, wherein the mass ratio of the prepolymer masterbatch component A to the mixed solution component B containing amines is 100:(40-50); The prepolymer masterbatch component A comprises the following components premixed together in a mass ratio of (80-100):(1-10):(1-5):prepolymer, organic solvent and dye; The mixed solution B containing amines comprises the following components pre-mixed together in a mass ratio of (15-35):(1-5):(1-10): a composite cross-linking agent, a composite catalyst and a composite flame retardant antistatic agent; The reactive mixed solution component C includes the following components in a mass ratio of (1-2):(1-2):(0.5-3):(0.2-0.8):(1-3):(40-50):(40-50):trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate, fumed silica, ethyl acetate and trichloroethylene.

2. The flame retardant polyurethane repair adhesive according to claim 1, characterized in that: The prepolymer is an isocyanate-terminated polymer material with a molecular weight of 500-3000, which is formed by the reaction of diols and diisocyanates.

3. The flame retardant polyurethane repair adhesive according to claim 1, characterized in that: The organic solvent includes one or more of ethyl acetate, isobutyl acetate, butanone, and methyl isobutyl ketone.

4. The flame retardant polyurethane repair adhesive according to claim 1, characterized in that: The coloring agent includes one of carbon black N330 and carbon black N550.

5. The flame retardant polyurethane repair adhesive according to claim 1, characterized in that: The composite cross-linking agent comprises the following components pre-mixed together in a mass ratio of (5-10):(5-10):(5-15):(2-5): a solid amine cross-linking agent, a liquid amine cross-linking agent, ethyl acetate and trichloroethylene; The solid amine cross-linking agent includes one or more of 3,3'-dichloro-4,4'-diaminodiphenylmethane, 4,4'-bis-sec-butylaminodiphenylmethane, N,N'-bis-sec-pentylcyclohexanediamine, and pentaerythritol; The liquid amine crosslinking agent includes one or more of dimethylthiotoluene diamine, 2,4-diamino-3,5-dimethylthiotoluene, N,N-bis(2-hydroxypropyl)aniline, and N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine.

6. The flame retardant polyurethane repair adhesive according to claim 1, characterized in that: The composite catalyst comprises the following components pre-mixed together in a mass ratio of (0.5-3): (0.5-3): an organic metal catalyst and a defoaming agent; The organometallic catalyst includes one or more of zinc isooctanoate, dibutyltin dilaurate, lithium isooctanoate, and lead isooctanoate; The defoaming agent includes one or more of a silicone resin defoaming agent, a methanol defoaming agent, an ethanol defoaming agent, an isopropanol defoaming agent, a polypropylene glycol defoaming agent, a n-butanol defoaming agent, and a tributyl phosphate defoaming agent.

7. The flame retardant polyurethane repair adhesive according to claim 1, characterized in that: The composite flame retardant and antistatic agent comprises the following components pre-mixed together in a mass ratio of (1-5): (1-3): (1-3): phosphorus-based flame retardant, antistatic agent and carbon black VXC72; The phosphorus-based flame retardant includes one or more of tris(2-chloroethyl)phosphate, tris(2-chloropropyl)phosphate, dimethyl methylphosphonate, and diethyl ethylphosphate; The antistatic agent includes one or more of antistatic agent KJ-100, antistatic agent KJ-150, and antistatic agent KJ-208.

8. A method for repairing rubber using the flame retardant polyurethane repair adhesive according to claim 1, characterized in that: The repair method comprises the following steps: S1. First, use a solvent to clean the rubber surface to be repaired, and then polish the rubber surface to be repaired to remove the residual rubber and oil on the surface; S2. Prepare the following components in a mass ratio of (1-2):(1-2):(0.5-3):(0.2-0.8):(1-3):(40-50):(40-50):trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate, fumed silica, ethyl acetate and trichloroethylene; uniformly mix ethyl acetate and trichloroethylene to form a premixed solvent; dissolve trichloroisocyanuric acid, chlorobromoisocyanuric acid, No. 70 chlorinated paraffin, zinc methacrylate and fumed silica in the premixed solvent and mix well to obtain a mixed solution component C containing reactive activity; S3, evenly apply the reactive mixed solution component C to the polished part of the rubber surface to be repaired, and apply 1 to 3 ml of the reactive mixed solution component C per 100 square centimeters of area each time. Apply it again after the first application, and dry it naturally after each application to increase the adhesion between the polyurethane and the surface to be repaired; S4, mixing the mixed solution component B containing amines and the prepolymer masterbatch component A in a mass ratio of (40-50):100 to form a polyurethane; S5. Apply a thin layer of the freshly mixed polyurethane to the polished area on the rubber surface to be repaired, let it stand for 0.5 to 5 minutes, pour the remaining polyurethane on the polished area on the rubber surface to be repaired, and the repair is completed after the polyurethane solidifies.